Cycling cadence alters exercise hemodynamics - Gotshall, R. W.; Bauer, T. A.; Fahrner, S. L. (International Journal of Sports Medicine, 1996)
Previous studies on cycling cadence have focused on the economy of the cadence, in search of the optimal pedal cadence. The purpose of this study was to determine the hemodynamic changes associated with varying pedal cadence at a constant workload. It was hypothesized that increased pedal cadence would enhance the skeletal muscle pump, resulting in elevation of cardiac output. Seven cyclists were enlisted to cycle at 200 watts at pedal cadences of 70, 90 and 110 rpm (random order). Oxygen uptake, heart rate, stroke volume, cardiac output, blood pressure, and vascular resistance were determined. As has been previously shown, oxygen uptake increased with increased cadence (70, 90, 110 rpm) at this workload. Heart rate, stroke volume, cardiac output and blood pressure were increased, and vascular resistance decreased, with increased cadence. Cardiac output increased (34%) in excess of the increase in oxygen uptake (15%) as shown by the decrease (-14.5%) in the arterial-venous oxygen difference occurring with increasing cadence. Apparently, even though the workload was constant, the increase in pedal cadence resulted in a more effective skeletal-muscle pump which increased muscle blood flow and venous return. It is not known if this might contribute to the natural selection of higher cadences by cycling athletes, even though there is reduced economy.